THE EFFICIENCY OF USING VISUAL LEARNING MEDIA IN IMPROVING THE UNDERSTANDING OF SCIENCE CONCEPTS IN ELEMENTARY SCHOOL STUDENTS - Muhammad Arsyad; Mujahiddin; Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2024)
Understanding science concepts at the primary school level is an important foundation for students' future science literacy development. However, the abstract characteristics of some science concepts are often a challenge for primary school students to understand. Visual learning media comes as a potential solution to bridge the gap between abstract concepts and students' concrete understanding. The research method in this study uses literature research method. The results show that the appropriate use of visual media can significantly improve students' understanding of complex science concepts. The efficiency of using visual media depends on several factors, including suitability to the material, attractive design, and effective integration in the learning process. Meanwhile, challenges in the implementation of visual media in primary schools, such as limited resources and teacher training needs.